MENGENAL MENSTRUASI DALAM PRESPEKTIF IMAM SYAFI’I - Imas Jihan Syah (Akademika, 2017)
Biologically, menstruation is a reproductive cycle showing that a woman is healthy related to her reproductive organs. Menstruation indicates a woman's sexual maturity in the sense that she has an ovum ready to be fertilized, be pregnant, and give birth to a child. In religious language we call this cycle as menstruation. In the Shafi'i school of thought (madzhab), women start menstruation period, at least age 9 (nine) years. The duration of menstruation is at least one day and night or 24 hours and at most is 15 days and nights. The menstrual discharge are commonly 6 or 7 days and nights. But in general, menstruation occurs 1x in a month. As for the most period there is no limit (according to ijma'). It could be 1x a year and even there is a woman who has never experienced menstruation throughout life, namely: Sayyidah Fatimah Az-Zahra Al-Battul.